Micro shear bond strength of mineral trioxide aggregate to different innovative dental restorative materials - DURMAZPINAR, PARLA MEVA (My University, 2023)
The objective of this in vitro study was to investigate the micro shear bond strength (µSBS) of mineral trioxide aggregate to four different restorative materials. Sixty mineral trioxide aggregate (MTA) samples were randomly assigned into four experimental groups based on the restorative materials used: nanohybrid resin composite as a control, giomer, alkasite and ormocer. µSBS samples were prepared for each group (n = 15). These samples were then submitted to a µSBS test (crosshead speed, 0.5 mm/min). The resulting data were statistically analyzed by one-way analysis of variance (ANOVA), Levene, and Bonferroni tests (α = 0.05). The bond strength of the alkasite group was statistically significantly higher than all the tested groups (p 0.05). Within the limitations of this study, alkasite restorative material could be a promising material when placed over MTA.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, MEKANİK; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, MECHANICAL; Makine Mühendisliği; Fizik Bilimleri; Mechanical Engineering; Physical Sciences; Microshear bond strength; mineral trioxide aggregate; optical microscopy; resin composites; restorative materials